Case Report: Multidisciplinary management and nursing care for a preterm infant with rare extrarenal malignant rhabdoid tumor: a clinical case study - Zhou, Qiaojia; Lü, Yuanhong; Chen, Mingna; Zhang, Lu; Chen, Qiong; Li, Yuan; Zhou, Queyun; Huang, Xi (Frontiers in Pediatrics, 2025)
ObjectiveTo report the multidisciplinary management and perioperative nursing strategies for a preterm infant with extrarenal malignant rhabdoid tumor complicated by fungal infection of the tumor, and to evaluate the effectiveness of humanistic care measures for the family facing a fatal outcome due to malignancy.MethodsThis paper reports the perioperative management and nursing care of a preterm infant with extrarenal malignant rhabdoid tumor using a case study approach. Preoperatively, the management included aggressive anti-infective therapy and isolation measures were applied to prevent fungal transmission, while a multidisciplinary team collaborated to develop a personalized skin management plan to preserve tumor integrity. Postoperatively, comprehensive care measures were implemented, including prevention of perioperative hypothermia, control of wound infection, and refined pain management. During hospitalization, attention was given to the psychological needs of the patient's parents, providing humanistic care and early identification to reduce the risk of maternal post-traumatic stress disorder (PTSD). After discharge, individualized guidance and follow-up home visits were provided to ensure continuity of care, with the medical team, nurses, and family working together to extend the infant' s survival and improve quality of life.ResultsThe infant's preoperative condition was effectively managed; the fungal infection was controlled with no nosocomial transmission, and tumor integrity was preserved without new ulcerations. Postoperatively, the infant's physiological functions improved significantly, with no instances of hypothermia or wound infection. Pain scores were successfully maintained at mild-to-moderate levels. The humanistic care approach was associated with positive psychosocial outcomes; the mother's anxiety score decreased from 31 to 17 by discharge, and the parents demonstrated calm acceptance of the infant's prognosis. The infant showed good growth, reaching 4.9 kg at two months of age. Ultimately, the infant survived for 214 days, passing away on February 17, 2024, from tumor recurrence with intracranial metastasis.ConclusionA comprehensive, multidisciplinary management approach is critical for rare and aggressive neonatal tumors. In this case, targeted perioperative nursing strategies played a vital role in controlling infection, preserving tumor integrity, and stabilizing the infant's physiological functions. Furthermore, integrated humanistic care was essential in alleviating family psychological stress and improving the infant's quality of life. This case provides a valuable reference for the integrated medical and nursing care of similar challenging cases.